2019
DOI: 10.4028/www.scientific.net/ddf.396.32
|View full text |Cite
|
Sign up to set email alerts
|

3-D Scale Model Study of Wave Run-Up, Overtopping and Damage in a Rubble-Mound Breakwater Subject to Oblique Extreme Wave Conditions

Abstract: A set of scale-model tests carried out to enlarge the range of wave steepness values analysed in run-up, overtopping and armour layer stability studies, focusing on oblique extreme wave conditions and on their effects on a gentler slope breakwater’s trunk armour and roundhead, is presented in this paper. A stretch of a rubble mound breakwater (head and part of the adjoining trunk, with a slope of 1(V):2(H)) was built in a wave basin at the Leibniz University Hannover to assess, under extreme wave conditions (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Beyond these geoscientific objectives, the Smartstone probe was successfully used in experiments focussing on coastal-engineering and hydro-engineering problems. Santos et al (2019) briefly reported experiments to investigate the stability of breakwater amour units. By means of the Smartstone probe data, Ravindra et al (2020) presented a detailed analysis of the failure mechanism of placed riprap on laboratory dam models.…”
Section: Potentials Of the Smartstone Probementioning
confidence: 99%
See 1 more Smart Citation
“…Beyond these geoscientific objectives, the Smartstone probe was successfully used in experiments focussing on coastal-engineering and hydro-engineering problems. Santos et al (2019) briefly reported experiments to investigate the stability of breakwater amour units. By means of the Smartstone probe data, Ravindra et al (2020) presented a detailed analysis of the failure mechanism of placed riprap on laboratory dam models.…”
Section: Potentials Of the Smartstone Probementioning
confidence: 99%
“…The spatiotemporal progression of moving slope material is the subject of research in various geoscientific disciplines (e.g. Wang et al, 2018;Aaron and McDougall, 2019;Schilirò et al, 2019). Laboratory experiments are a wellestablished instrument to investigate the physical behaviour of landslide motion processes.…”
Section: Introductionmentioning
confidence: 99%
“…The total model is 9.0m long, 0.82m high and 3.0m wide. Details of the model can be found at the data storage report (Santos et al 2019). The waves in the model were measured with arrays made of six acoustic wave probes.…”
Section: Breakwater Modelmentioning
confidence: 99%
“…The influence of high incidence angles (very oblique waves) on breakwaters is unknown, as limited data is available. The accepted climate change scenarios, which report sea level rise (Weisse et al, 2014), causing different conditions of incident wave angles on breakwaters, foster the study of very oblique waves in what concerns both their characterization as well as their influence on rubble-mound breakwaters within RodBreak experimental work (Santos et al, 2019a). RodBreak main goal was to contribute to a new whole understanding of the phenomena filling existing data gaps in the R&D&I, to enable the mitigation of future sea level rise in European coastal structures (Santos et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…The accepted climate change scenarios, which report sea level rise (Weisse et al, 2014), causing different conditions of incident wave angles on breakwaters, foster the study of very oblique waves in what concerns both their characterization as well as their influence on rubble-mound breakwaters within RodBreak experimental work (Santos et al, 2019a). RodBreak main goal was to contribute to a new whole understanding of the phenomena filling existing data gaps in the R&D&I, to enable the mitigation of future sea level rise in European coastal structures (Santos et al, 2019b). This includes the run-up and overtopping characterization on rough and permeable slopes, as well as to check and extend the validity range of the formulas developed for armour layer stability, focusing on oblique extreme wave conditions and on their effects on a gentler slope breakwater's trunk and roundhead.…”
Section: Introductionmentioning
confidence: 99%